Diversifikasi Produk Olahan Buah Mangrove Dau (Bruguiera Gymnoorhiza) Untuk Cake Gulmerda Dan Sirup Dau Di Desa Maitara Utara Kota Tidore Kepulauan - Rina Rina; Salim Abubakar; Masykhur Abdul Kadir; Adi Noman Susanto; Ariyati H. Fadel; Fajria Dewi Salim; Mesrawaty Sabar; Riyadi Subur; Sri Endah Widiyanti (Jurnal Pengabdian Magister Pendidikan IPA, 2021)
Mangrove forests are biological resources found in coastal areas that have ecological and economic functions. Bruguiera gymnorrhiza is a type of mangrove that grows in the middle and back zones with a muddy sand substrate. The fruit can be used as a local food source, especially in coastal areas that have the potential of mangrove forests, but of course must pay attention to the sustainability of the mangrove ecosystem. This PKM aims to apply the technology of processing the Bruguiera gymnorrhiza mangrove fruit for gulmerda cake and syrup which has a high selling value. The methods used in the Community Partnership Program (PKM) activities are lectures, practice, hedonic testing and mentoring. The results of PKM have increased public knowledge in utilizing raw materials that are around their environment to be processed into products that have a selling value, motivating people to be more independent and confident in developing businesses to improve community welfare, organoleptic testing, Cake gulmerda products are products that have higher score. The formation of the entrepreneurial group "Let's Feel Creative" in the context of the sustainability of training activities.Keywords: Diversification, processed mangrove fruit, gulmerda cake, Dau syrup, North Maitara